Peran Gaya Hidup Dalam Memoderasi Pengaruh Penggunaan E-Wallet Terhadap Perilaku Konsumtif Mahasiswa - Mila Septy Fiani Zustika Sari; Shanti Nugroho Sulistyowati (ARBITRASE: Journal of Economics and Accounting, 2026)
The rapid development of digital financial technology has transformed transaction patterns and consumer behavior, particularly among university students who actively utilize electronic wallet (e-wallet) services. Transaction convenience, payment efficiency, and various digital promotional features are considered capable of increasing students’ consumptive behavior. This study aims to examine the influence of e-wallet usage on consumptive behavior with lifestyle as a moderating variable among students at Universitas PGRI Jombang. The study employed a quantitative approach using an explanatory research design. Data were collected through online questionnaires distributed to 272 respondents selected using the Slovin formula from a total population of 837 students. Data analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with SmartPLS 3 software. The analytical procedures included descriptive statistical analysis, outer model testing, inner model evaluation, hypothesis testing, and moderating effect analysis. The findings revealed that e-wallet usage had a positive and significant effect on students’ consumptive behavior, indicated by a path coefficient of 0.530 and a p-value of 0.000. Lifestyle also showed a positive and significant influence on consumptive behavior with a coefficient value of 0.339 and a p-value of 0.000. Furthermore, lifestyle significantly moderated the relationship between e-wallet usage and consumptive behavior with a coefficient value of 0.148 and a p-value of 0.001. The novelty of this study lies in the integration of e-wallet usage and lifestyle variables in explaining students’ consumptive behavior in the digital era. This research contributes theoretically to the development of digital consumer behavior studies and practically to improving students’ financial literacy in the wise use of digital payment technology.